High plasma levels of vitamin C and E are associated with incident radiographic knee osteoarthritis. - Chaganti, R; Tolstykh, I; Javaid, M; Neogi, T; Torner, J; Curtis, J; Jacques, P; Felson, D; Lane, N; Nevitt, M (2014)
BACKGROUND: Previous studies suggest that the antioxidants vitamins C and E may protect against development of knee osteoarthritis (OA). We examined the association of circulating levels of vitamin C and E with incident whole knee radiographic OA (WKROA). METHODS: We performed a nested case-control study of incident WKROA in MOST, a cohort of 3,026 men and women aged 50-79 years with, or at high risk of, knee OA. Incident cases were knees without either tibiofemoral (TF) or patellofemoral (PF) OA at baseline that developed TF and/or PF OA by 30-month follow-up. Two control knees per case were selected from those eligible for WKROA that did not develop it. Vitamin C and E (alpha-tocopherol) assays were done on baseline supernatant plasma (PCA) and serum samples, respectively. We examined the association of gender-specific tertiles of vitamin C and E with incident WKROA using logistic regression with GEE, adjusting for age, gender, and obesity. RESULTS: Subjects without WKROA at baseline who were in the highest tertile of vitamin C had a higher incidence of WKROA [adjusted OR = 2.20 (95% CI: 1.12-4.33); P-value = 0.021], with similar results for the highest tertile of vitamin E [adjusted OR = 1.89 (1.02-3.50); P-value = 0.042], compared to those in the lowest tertiles. P-values for the trend of vitamin C and E tertiles and incident WKROA were 0.019 and 0.030, respectively. CONCLUSIONS: Higher levels of circulating vitamin C and E did not provide protection against incident radiographic knee OA, and may be associated with an increased risk of knee OA.